1994
DOI: 10.1071/pp9940901
|View full text |Cite
|
Sign up to set email alerts
|

The Heat-Shock Response Relevant to Molecular and Structural Changes in Wheat Yield and Quality

Abstract: When wheat coleoptiles or plants are subjected to a period of heat stress (e.g, at > 35�C for 1 h or more), there is a reduction in normal protein synthesis, accompanied by de novo synthesis of the classical range of heat-shock proteins (based on radioactive tracer experiments) in virtually all parts of the plant. Study of coleoptile elongation rates indicates that this synthesis is related to a protective effect, whereby a preliminary heat shock provides a degree of protection against a later lethal shock.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 7 publications
1
18
0
2
Order By: Relevance
“…Starch granule size is known to be affected by environmental conditions (Blumenthal et al 1994;Panozzo and Eagles 1998) and the observations here confirm that association. Our data are also consistent with the observations in barley of Borem et al (1999) who identified QTLs for a number of starch granule traits on chromosomes 2 and 4 (2H and 4H).…”
Section: Discussionsupporting
confidence: 87%
“…Starch granule size is known to be affected by environmental conditions (Blumenthal et al 1994;Panozzo and Eagles 1998) and the observations here confirm that association. Our data are also consistent with the observations in barley of Borem et al (1999) who identified QTLs for a number of starch granule traits on chromosomes 2 and 4 (2H and 4H).…”
Section: Discussionsupporting
confidence: 87%
“…The experimental conditions are described in the accompanying paper by Blumenthal et al (1994). Overall, there was a weakening of dough strength in that the mean resistance breakdown (Mixograph) for the set of 45 wheats increased from 16 to 19 ( P < 0.001) as a result of heat stress, and the time to peak resistance fell from 253 s (control mean) to 221 s (P < 0.001).…”
Section: Minimising the Effects Of Stress On Grain Qualitymentioning
confidence: 96%
“…An important part of this process will be the elucidation of the molecular mechanism involved in heat stress and its effect on grain quality (Blumenthal et al 1994). The existence of heat-stress elements upstream of the coding regions for gluten genes is part of this molecular mechanism, and there will be opportunities to screen for this tolerance using these nucleotide sequences as the basis for gene probing.…”
Section: Minimising the Effects Of Stress On Grain Qualitymentioning
confidence: 99%
“…1994), hence samples with low swelling powers would be of interest for that end use. Starch granule size distribution is affected by both genotype (Stoddard 2000(Stoddard , 2003 and environment (Blumenthal et al 1994(Blumenthal et al , 1995. The B granule content of hexaploid wheat starch is commonly around 30% by volume (Hughes and Briarty 1976;Brocklehurst and Evers 1977;Evers and Lindley 1977) and surveys have shown values as low as 13% (Soulaka and Morrison 1985) and as high as 47% (Stoddard 1999).…”
Section: Starch Characterisationmentioning
confidence: 98%